2019
DOI: 10.1016/j.jpainsymman.2019.06.005
|View full text |Cite|
|
Sign up to set email alerts
|

Palliative Care Transitions From Acute Care to Community-Based Care—A Systematic Review

Abstract: Context. Although the literature on transitions from hospital to the community is extensive, little is known about this experience within the context of palliative care (PC).Objective. We conducted a systematic review to investigate the impact of receiving palliative care in hospital on the transition from hospital to the community.Methods. We systematically searched MEDLINE, Embase, ProQuest, and CINAHL from 1995 until April 10, 2018, and extracted relevant references. Eligible articles were published in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…However, as only two studies assessed this outcome, there is a need for further research in this area. Similar to our findings, a recent systematic review by Saunders et al (2019), examining adults with malignant or mixed malignant-non-malignant diseases and reporting outcomes of palliative care transitions from acute to community-based care including LOS, discharge support and hospital readmissions, concluded that the evidence for their effectiveness were limited due to heterogeneity of study designs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, as only two studies assessed this outcome, there is a need for further research in this area. Similar to our findings, a recent systematic review by Saunders et al (2019), examining adults with malignant or mixed malignant-non-malignant diseases and reporting outcomes of palliative care transitions from acute to community-based care including LOS, discharge support and hospital readmissions, concluded that the evidence for their effectiveness were limited due to heterogeneity of study designs.…”
Section: Discussionsupporting
confidence: 88%
“…This may mean that important studies may not have been included. However, we are encouraged that the systematic review by Saunders et al (2019) similarly found few papers on the topic. Secondly, methodological and overall reporting quality of the included studies ranged between 50 and 98% according to the CCAT assessment, suggesting considerable variability in their quality.…”
Section: Discussionmentioning
confidence: 99%
“…Another point of concern is the influence of the CCB population characteristics such as the high age, the high level of comorbid diseases and the level of frailty, on the intervention fidelity, which should not be underestimated (Jepma et al, submitted). The included population, those who were in an advanced stage of disease and beyond the point of no return, might have benefitted more from advance care planning and end‐of‐life transitional care interventions (Saunders et al., 2019; Wong et al., 2016). The feasibility of the intervention components needs to be reconsidered from this perspective as well.…”
Section: Discussionmentioning
confidence: 99%
“…These findings corroborate findings from other studies where technologies assisting care at home are still not optimal 45 . Hence, organizations need to improve technological advancement through policies that enable access to medical records across inter-departments or develop shared access to electronic health records that would allow ease of communication and collaboration among healthcare professionals, patients, and their family members 46 , 47 . Future HaH should also consider incorporating and evaluating the effectiveness of remote vital signs monitoring and virtual physician visits to improve technology integration in HaH.…”
Section: Discussionmentioning
confidence: 99%